Pengaruh Persepsian Risiko, Kepuasan dan Citra Harga Terhadap Niat Membeli Ulang Menggunakan M-Commerce di Kalangan Masyarakat Kota Sungai Penuh, dengan Kepercayaan dan Sensitivitas Harga Sebagai Moderasi - Edia Satria (Jurnal Indonesia Sosial Teknologi, 2022)
The use of mobile devices such as smartphones and tablets, which is increasingly widespread throughout the world, is currently at an all-time high. This technological disruption makes mobile e-commerce or m-commerce a business channel that is considered more convenient and efficient for today's lifestyle compared to e-commerce or offline stores. This study aims to determine the effect of perceived risk, satisfaction and price image on repurchase intention using m-commerce among the people of Sungai Penuh City, with trust and price sensitivity as moderating. This study uses the Smart PLS software data analysis method. Research This research was conducted in the urban area of ​​Sungai Penuh City in 2021. The population in this study was the Sungai Penuh City Community who had shopped through m-commerce at least once. The results of this study state that perceived risk has no significant effect on repurchase intentions using m-commerce. Price image also has a positive and significant effect on repurchase intention using m-commerce. Whether consumer confidence in m-commerce is higher or lower, the perceived risk still has no impact on repurchase intentions using m-commerce. The second moderating effect of this study is the moderation of price sensitivity to the effect of price image on repurchase intention which results in no function.